Growth and yield of strawberry plants fertilized with nitrogen and phosphorus - Reinaldo F. Medeiros; Walter E. Pereira; Rummenigge de M. Rodrigues; Ronaldo do Nascimento; Janivan F. Suassuna; Tony A. G. Dantas (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACTStrawberry (Fragaria x ananassa) is a crop that has rapid growth and is highly influenced by fertilization. Due to its development speed, the plant needs to absorb sufficient macronutrients in order to meet its demand. The objective of this research was to evaluate growth and yield of strawberry under different doses of nitrogen (N), phosphorus (P) and potassium (K) fertilization. The treatments, using Box's central composite design, were distributed in randomized blocks with four replicates and consisted of five N doses (0.16, 0.37, 0.88, 1.4 and 1.6 g plant-1) and five P doses (0.3, 0.58, 1.2, 1.8 and 2.1 g plant-1), in the presence (1.67 g plant-1) and absence of K. Seedlings of the cultivar 'Oso Grande' were cultivated in 10-L pots. The analysed variables were: plant height, fresh fruit mass, number of leaves, number of fruits, total soluble solids and titratable acidity. The fertilization with N and P increased the values for most of the studied variables. At the highest doses of N and P, K stimulated plant yield.